PENGARUH KUALITAS PELAYANAN JASA TRANSPORTASI UMUM TERHADAP LOYALITAS PELANGGAN PADA BUS TRANS MAMMINASATA KOTA MAKASSAR - Alfidia Sutendy , Anggun; Zelfia, Zelfia; Muttaqin Mustari , Andi (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This script discusses the influence of the quality of public transportation services on customer loyalty on the Trans Mamminasata Bus. The main problem is how the influence of the quality of transportation services on customer loyalty on the Trans Mamminasata Bus and what are the stages in the formation of the Trans Mamminasata Bus. This study aims to determine whether the targets, duties, and responsibilities have been carried out properly, it is necessary to measure the success of Service Quality on Customer Loyalty on the Trans Mamminasata Bus. The type of research used is descriptive research method with quantitative approach. This research lasted for one month located in the Trans Mamminasata Bus corridor on Boulevard road in front of the Panakukang Mall Makassar, with customer informants using the Trans Mamminasata Bus transportation service. The results of this study were conducted to obtain the expected Customer Loyalty of Trans Mamminasata Bus Users, from the study of the variabels that affect customer loyalty is the quality of service (X1). Hypothesis testing shows that Service Quality has an effect on Customer Loyalty for Trans Mamminasata Bus Users.